Efektivitas Berbagai Dosis Plant Growth Promoting Rhizobacteria (PGPR) Multi Mikro Organisme untuk Mengoptimalkan Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomoea reptans Poir.) Organik - Nuning Indri Astutie; Mariyatul Qibtiyah; Dian Eka Kusumawati; Istiqomah Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Land kale plants are one of the vegetables that are in great demand by almost all people. Short-lived plants have the ability to respond quickly when given growth activators. In Indonesia, kale has a very potential market and prices tend to be stable. Although the consumption of kale is quite high, the amount of production produced has not been able to fulfil the demand, so an increase in kale productivity is needed. Steps that can be taken are to focus on improving the planting process, such as the application of PGPR. The study aimed to explore the effect of various doses of PGPR Multi Microorganisms on the growth and production of Organic Land Kale Plants. For this analysis, a one-factor Randomised Group Design method was used, consisting of six levels of PGPR dosage, with four repetitions including: no PGPR; 6 l/ ha; 8 l/ ha; 10 l/ ha; 12 l/ ha; 14 l/ ha. Wet weight per hectare, wet weight per plot, number of leaves, and plant height were the parameters observed. The results of the observations were tested with Fisher's 5% level, if there was a significant difference, the 5% BNT test was continued. The results showed that the dose of 8 l/ha gave the best results among other PGPR doses on the production of ground kale.